Imdeduya. Variants of a myth of love and hate from the Trobriand Islands of Papua New Guinea - Gunter Senft (Culture and Language Use. Studies in Anthropological Linguistics, 2017)
This volume presents five variants of the Imdeduya myth: two versions of the actual myth, a short story, a song and John Kasaipwalova's English poem "Sail the Midnight Sun". This poem draws heavily on the Trobriand myth which introduces the protagonists Imdeduya and Yolina and reports on Yolina's intention to marry the girl so famous for her beauty, on his long journey to Imdeduya's village and on their tragic love story. The texts are compared with each other with a final focus on the clash between orality and scripturality. Contrary to Kasaipwalova's fixed poetic text, the oral Imdeduya versions reveal the variability characteristic for oral tradition. This variability opens up questions about traditional stability and destabilization of oral literature, especially questions about the changing role of myth - and magic - in the Trobriand Islanders' society which gets more and more integrated into the by now "literal" nation of Papua New Guinea.